Character Design for the Illustrated Book “Tukang Pos Pembawa Mimpi” - Brilliant Firdaus Ramadhani; Aninditya Daniar; Masnuna Masnuna (Gorga : Jurnal Seni Rupa, 2025)
Character design is a crucial visual element in media, particularly illustrated books. “Tukang Pos Pembawa Mimpi” is an illustrated book that explores themes of dreams and aspirations for teenagers aged 16-18. The story follows a postman who guides readers on a journey of self-discovery to help them find their dreams. This study aims to develop a character design for a 16-year-old postman to be utilized in an illustrated book. The research methodology employed is a descriptive qualitative approach, utilizing observation, analysis, and interviews. The resulting character design possesses high visual appeal and effectively caters to the target audience’s age, thereby fostering their interest in reading the book’s content. The character adopts a cartoonish style and exudes a friendly demeanor.